Lowering sugars in dark chocolate through alternative sweeteners - Arentz, Heather Marie (Kansas State University, 2018)
With the recent new food labeling guidelines requiring that added sugars be listed on nutrition labels, both consumers and the food industry are concerned about sugar and added sugars in food. The literature review in this report evaluated studies that focused on a reduction of sugar in chocolate, a popular food that many people associate with containing sugar. The studies reviewed here included reduced sugar or sugar-free chocolates that used polyols, rare sugar, inulin, and high-potency sweeteners. Rare sugars are monosaccharides and their derivatives, which are rarely found in nature. One rare sugar that was included in the literature review was D-allulose. The review also looked at models of reducing added sugars in foods. From the review, a study was conducted to look at different sweeteners in dark chocolate. In this study, agave and fructose were compared to the control (sucrose); the reduction of sucrose in samples in this study was 30% from the control. The study evaluated how the sweeteners affect the physical attributes of dark chocolate to determine the best sweetener to use to reduce sucrose and further reduce added sugar. The study found that lowering sugar for taste is not the only aspect a product developer must consider when reducing sugar in a product; different sweeteners also affect physical parameters in chocolate. For example, the moisture and particle size distribution affect the physical properties of the chocolate. The moisture in the agave-sweetened chocolate bar was 54.54% higher than in the sucrose-sweetened chocolate bar; the agave-sweetened bar was 41.67% higher in moisture than the fructose-sweetened chocolate bar. The higher moisture of the agave-sweetened chocolate samples resulted in higher agglomeration; moisture created sticky patches that induced agglomeration and a higher reduction of particles. The hygroscopicity of agave affected the rheology of the chocolate because higher agglomeration of particles leads to higher yield values in the agave-sweetened chocolate. The smaller particles have more surface area to get coated in fat, which affects rheology. The sucrose-sweetened chocolate treatment, which had larger particles and lower surface area, had a higher viscosity. However, the agave- and fructose-sweetened chocolates made in this study can be considered standard of identity while non-nutritive sweeteners would not be. When developing new chocolate formulations with reduced sugar, the scientist needs take the physical parameters of the non-sucrose sugars used into account.
Keywords: sweetener; chocolate; sugar